2016
DOI: 10.1080/87565641.2016.1170835
|View full text |Cite
|
Sign up to set email alerts
|

The Test–Retest Reliability of the Visually Evoked Contingent Negative Variation (CNV) in Children and Adults

Abstract: Establishing the reliability of event-related potentials is critical for future applications to biomarker development and clinical research. Few studies have examined the reliability of the contingent negative variation (CNV), and only in adults. The current study explored test-retest reliability of the visually evoked CNV and its embedded components, the O-wave and the E-wave, in children (7-13 years) and young adults (19-28 years) during a visual Go/No-Go task over 1-2 weeks. Test-retest reliability of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
(57 reference statements)
4
17
1
Order By: Relevance
“…Consequently, for both cue‐P300 and iCNV at follow‐up, there was more variance left that could be explained by other variables. This should not erroneously be interpreted as a comparatively low temporal stability, as correlations of similar magnitude have been reported in a study investigating the test–retest reliability of CNV and its components after 2 weeks in children (Taylor et al., ). A lower temporal stability of the assessed ERP components compared to reaction time may rather be attributed to developmental changes in task preparation in the transition from childhood to adolescence (Jonkman, ; Jonkman et al., ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Consequently, for both cue‐P300 and iCNV at follow‐up, there was more variance left that could be explained by other variables. This should not erroneously be interpreted as a comparatively low temporal stability, as correlations of similar magnitude have been reported in a study investigating the test–retest reliability of CNV and its components after 2 weeks in children (Taylor et al., ). A lower temporal stability of the assessed ERP components compared to reaction time may rather be attributed to developmental changes in task preparation in the transition from childhood to adolescence (Jonkman, ; Jonkman et al., ).…”
Section: Discussionsupporting
confidence: 65%
“…Similar to previous studies, which employed the same task, the mean amplitude of the iCNV was calculated for the latency range from −1,500 to −1,000 ms relative to S2 onset (Kamijo et al., ; Ludyga, Gerber, et al., ; Ludyga, Herrmann, et al., ). As these studies observed a central distribution of the iCNV elicited from the Sternberg task and acceptable test–retest reliability has been reported for this region (Taylor, Gavin, & Davies, ), the average of Cz, C1, and C2 was extracted for statistical analyses. Based on previous studies and own experience, the amplitudes at Pz, P1, and P2 over the latency range from 300 to 600 ms after S1 were averaged to derive the cue‐P300.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, during a typical CNV paradigm, the first stimulus will inform the participant if they will or will not perform a set action when the second stimulus is presented. During trials where the Stimulus 1 prompts the participant to prepare to perform the action upon presentation of Stimulus 2 (known as go trials), an increasing negative drift is present in the EEG signal prior to task onset in comparison to "no-go" trials where Stimulus 1 prompts the participant to remain at rest for the trial duration (e.g., Taylor, Gavin, & Davies, 2016). However, Stimulus 1 may also serve as a general "prepare for action" prompt, with Stimulus 2 instructing the participant to go or not to go.…”
Section: The Cnvmentioning
confidence: 99%
“…However, Stimulus 1 may also serve as a general "prepare for action" prompt, with Stimulus 2 instructing the participant to go or not to go. During response preparation between Stimuli 1 and 2, the CNV may be divided into two phases, an early orienting phase known as the O-wave and a later expectancy and preparation phase known as the E-wave (e.g., J. F. Brunner et al, 2015;Taylor et al, 2016), both of which are influenced by cognitive and motor factors (e.g., Lukhanina, Karaban, Burenok, Mel'nik, & Berezetskaya, 2006). Specifically, the Owave is greatest at midline frontal electrodes and is associated with arousal and processing of stimulus characteristics such as intensity (e.g., Nagai et al, 2004), in addition to cognitive processes associated with categorical judgment (e.g., to "go" or "no-go"; Cui et al, 2000), and task maintenance and rehearsal (J. F. Brunner et al, 2015).…”
Section: The Cnvmentioning
confidence: 99%
“…Interestingly, a previous study involving children found that across two assessment sessions conducted one-to-two weeks apart, CNV E-wave amplitudes became more negative in the second session. Furthermore, this increased negativity occurs despite consistent behavioral performance suggesting that the children were equally attentive and successful in completing the task during each session (Taylor et al, 2016). Although the E-wave is known to become more negative across development (e.g., Hämmerer et al, 2010; Jonkman, 2006; Jonkman, Lansbergen & Stauder, 2003; Segalowitz & Davies, 2004; Taylor et al, 2016), it is unlikely that developmental changes occurred over such a short period of time (i.e., one or two weeks in school-aged children).…”
Section: Introductionmentioning
confidence: 99%